Combined directed ortho-zincation and palladium-catalyzed strategies: Synthesis of 4,n-dimethoxy-substituted benzo[b]furans - Guilarte, Verónica; Castroviejo, M. Pilar; Álvarez, Estela; Sanz, Roberto (Beilstein Journal of Organic Chemistry, 2011)
A new route to regioselectively dialkoxy-functionalized benzo[b]furan derivatives has been developed from 3-halo-2-iodoanisoles bearing an additional methoxy group, which have been accessed through an ortho-zincation/iodination reaction. Two palladium-catalyzed processes, namely a Sonogashira coupling followed by a tandem hydroxylation/cyclization sequence, give rise to new and interesting dimethoxy-substituted benzo[b]furans.
Keywords: benzo[b]furans; o-zincation; palladium; selectivity

Modern Arene Chemistry - Hartung, C. G.; Snieckus, V. (The Directed ortho Metalation Reaction – A Point of Departure for New Synthetic Aromatic Chemistry, 2002)

(untitled) - Whisler, M. C.; MacNeil, S.; Snieckus, V.; Beak, P. (Angew. Chem., Int. Ed., 2004)

Metal-Catalyzed Cross-Coupling Reactions - Anctil, E. J.-G.; Snieckus, V. (Wiley-VCH, 2004)

Handbook of C–H Transformations - Macklin, T.; Snieckus, V. (Wiley-VCH, 2005)

(untitled) - Eberhardt, G. G.; Butte, W. A. (J. Org. Chem., 1964)

(untitled) - Schlosser, M.; Choi, J. H.; Takagishi, S. (Tetrahedron, 1990)

(untitled) - Mulvey, R. E.; Mongin, F.; Uchiyama, M.; Kondo, Y. (Angew. Chem., Int. Ed., 2007)

(untitled) - Mulvey, R. E. (Acc. Chem. Res., 2009)

(untitled) - Kondo, Y.; Shilai, M.; Uchiyama, M.; Sakamoto, T. (J. Am. Chem. Soc., 1999)

(untitled) - Uchiyama, M.; Miyoshi, T.; Kajihara, Y.; Sakamoto, T.; Otani, Y.; Ohwada, T.; Kondo, Y. (J. Am. Chem. Soc., 2002)

(untitled) - Uchiyama, M.; Kobayashi, Y.; Furuyama, T.; Nakamura, S.; Kajihara, Y.; Miyoshi, T.; Sakamoto, T.; Kondo, Y.; Morokuma, K. (J. Am. Chem. Soc., 2008)

(untitled) - Naka, H.; Uchiyama, M.; Matsumoto, Y.; Wheatley, A. E. H.; McPartlin, M.; Morey, J. V.; Kondo, Y. (J. Am. Chem. Soc., 2007)

(untitled) - Usui, S.; Hashimoto, Y.; Morey, J. V.; Wheatley, A. E. H.; Uchiyama, M. (J. Am. Chem. Soc., 2007)

(untitled) - Clegg, W.; Dale, S. H.; Drummond, A. M.; Hevia, E.; Honeyman, G. W.; Mulvey, R. E. (J. Am. Chem. Soc., 2006)

(untitled) - Uchiyama, M.; Matsumoto, Y.; Nobuto, D.; Furuyama, T.; Yamaguchi, K.; Morokuma, K. (J. Am. Chem. Soc., 2006)

(untitled) - Uchiyama, M.; Matsumoto, Y.; Usui, S.; Hashimoto, Y.; Morokuma, K. (Angew. Chem., Int. Ed., 2007)

(untitled) - Kondo, Y.; Morey, J. V.; Morgan, J. C.; Naka, H.; Nobuto, D.; Raithby, P. R.; Uchiyama, M.; Wheatley, A. E. H. (J. Am. Chem. Soc., 2007)

(untitled) - Hevia, E.; Kennedy, A. R.; Klett, J.; McCall, M. D. (Chem. Commun., 2009)

(untitled) - De Luca, L.; Nieddu, G.; Porcheddu, A.; Giacomelli, G. (Curr. Med. Chem., 2009)

(untitled) - Hwu, J. R.; Chuang, K.-S.; Chuang, S. H.; Tsay, S.-C. (Org. Lett., 2005)

(untitled) - Hou, X.-L.; Yang, Z.; Yeung, K.-S.; Wong, H. N. C. (Prog. Heterocycl. Chem., 2009)

(untitled) - Yeung, K.-S.; Yang, Z.; Peng, X.-S.; Hou, X.-L. (Prog. Heterocycl. Chem., 2011)

(untitled) - Ober, A. G.; Fronczek, F. R.; Fischer, N. H. (J. Nat. Prod., 1985)

(untitled) - Parodi, F. J.; Fischer, N. H.; Flores, H. E. (J. Nat. Prod., 1988)

(untitled) - Wang, L.-Q.; Zhao, Y.-X.; Hu, J. M.; Jia, A.-Q.; Zhou, J. (Helv. Chim. Acta, 2008)

(untitled) - Stevenson, P. C.; Veitch, N. C. (Phytochemistry, 1998)

(untitled) - Joshi, A. S.; Li, X.-C.; Nimrod, A. C.; ElSholy, H. N.; Walker, L. A.; Clark, A. M. (Planta Med., 2001)

(untitled) - Kim, I.; Lee, S.-H.; Lee, S. (Tetrahedron Lett., 2008)

(untitled) - Youn, S. W.; Eom, J. I. (Org. Lett., 2005)

(untitled) - Heravi, M. M.; Sadjadi, S. (Tetrahedron, 2009)

(untitled) - Tsuchikama, K.; Hashimoto, Y.-k.; Endo, K.; Shibata, T. (Adv. Synth. Catal., 2009)

(untitled) - Alessi, M.; Larkin, A. L.; Ogilvie, K. A.; Green, L. A.; Lai, S.; López, S.; Snieckus, V. (J. Org. Chem., 2007)

(untitled) - Blanchet, J.; Macklin, T.; Ang, P.; Metallinos, C.; Snieckus, V. (J. Org. Chem., 2007)

(untitled) - Nerdinger, S.; Kendall, C.; Cai, X.; Marchart, R.; Riebel, P.; Johnson, M. R.; Yin, C.-F.; Hénaff, N.; Eltis, L. D.; Snieckus, V. (J. Org. Chem., 2007)

(untitled) - MacNeil, S. L.; Gray, M.; Gusev, D. G.; Briggs, L. E.; Snieckus, V. (J. Org. Chem., 2008)

(untitled) - James, C. A.; Snieckus, V. (J. Org. Chem., 2009)

(untitled) - James, C. A.; Coelho, A. L.; Gevaert, M.; Forgione, P.; Snieckus, V. (J. Org. Chem., 2009)

(untitled) - Sanz, R.; Castroviejo, M. P.; Fernández, Y.; Fañanás, F. J. (J. Org. Chem., 2005)

(untitled) - Sanz, R.; Castroviejo, M. P.; Guilarte, V.; Pérez, A.; Fañanás, F. J. (J. Org. Chem., 2007)

(untitled) - Sanz, R.; Guilarte, V.; Hernando, E.; Sanjuán, A. M. (J. Org. Chem., 2010)

(untitled) - Liang, Y.; Xie, Y.-X.; Li, J.-H. (J. Org. Chem., 2006)

(untitled) - Sanz, R.; Guilarte, V.; García, N. (Org. Biomol. Chem., 2010)

(untitled) - Guilarte, V.; Castroviejo, M. P.; García-García, P.; Fernández-Rodríguez, M. A.; Sanz, R. (J. Org. Chem., 2011)

(untitled) - Tlili, A.; Xia, N.; Monnier, F.; Taillefer, M. (Angew. Chem., Int. Ed., 2009)

(untitled) - Zhao, D.; Wu, N.; Zhang, S.; Xi, P.; Su, X.; Lan, J.; You, J. (Angew. Chem., Int. Ed., 2009)

(untitled) - Jing, L.; Wei, J.; Zhou, L.; Huang, Z.; Li, Z.; Zhou, X. (Chem. Commun., 2010)

(untitled) - Yang, D.; Fu, H. (Chem.–Eur. J., 2010)

(untitled) - Anderson, K. W.; Ikawa, T.; Tundel, R. E.; Buchwald, S. L. (J. Am. Chem. Soc., 2006)

(untitled) - Schulz, T.; Torborg, C.; Schäffner, B.; Huang, J.; Zapf, A.; Kadyrov, R.; Börner, A.; Beller, M. (Angew. Chem., Int. Ed., 2009)

(untitled) - Sergeev, A. G.; Schulz, T.; Torborg, C.; Spannenberg, A.; Neumann, H.; Beller, M. (Angew. Chem., Int. Ed., 2009)